1998
DOI: 10.1093/jn/128.9.1537
|View full text |Cite
|
Sign up to set email alerts
|

α-Linolenic Acid Deficiency Modifies Distractibility but Not Anxiety and Locomotion in Rats during Aging

Abstract: In rodents, chronic dietary alpha-linolenic acid deficiency decreases learning and memory and alters dopaminergic and serotoninergic neurotransmission. However, these two neurotransmitter systems are related mainly to attention, emotion and locomotion. Therefore, we decided to investigate the effects of dietary alpha-linolenic acid deficiency in rats tested with animal models of distractibility (the distractometer procedure), anxiety (the elevated plus maze) and ambulatory activity (a circular corridor). Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…These studies suggest that DHA deficiency during brain development may lead to irreversible damage to certain brain functions. In contrast, DHAdeficient mice or rats fed an n-3 fatty acid-deficient diet from the embryo throughout their entire life, as opposed to only in early life, as in this study, showed either no difference in or lower anxiety-like behavior in the plus-maze test and depressive-like behavior in the forced swimming task compared to animals fed an n-3 fatty acidadequate diet [44][45][46][47][48]. This may be partly due to the different experimental design regarding the period of DHA deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…These studies suggest that DHA deficiency during brain development may lead to irreversible damage to certain brain functions. In contrast, DHAdeficient mice or rats fed an n-3 fatty acid-deficient diet from the embryo throughout their entire life, as opposed to only in early life, as in this study, showed either no difference in or lower anxiety-like behavior in the plus-maze test and depressive-like behavior in the forced swimming task compared to animals fed an n-3 fatty acidadequate diet [44][45][46][47][48]. This may be partly due to the different experimental design regarding the period of DHA deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, various studies have shown different effects on anxiety behavior in animals after altering Ω-3:Ω-6 PUFA levels in their diet (Fedorova and Salem, 2006). Ω-3 deficient mice have previously been shown to have everything from decreased anxiety (Nakashima et al, 1993; Francès et al, 1995), increased anxiety (Carrié et al, 2000a; Fedorova and Salem, 2006), or no change in anxiety measured by time spent in the open arm of an elevated plus maze (Belzung et al, 1998; Moriguchi et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the amount of these FA in cell membranes could influence neurological processes that affect behavior. Previous studies in rats found that altered composition of n-3 FA in neurological membranes due to dietary insufficiency of ALA can influence both serotoninergic and dopaminergic neurotransmission (90,91). n-3 FA insufficiency has been associated with deficits in learning and memory (92), but effects on attention have not been as clear (93,94).…”
Section: Discussionmentioning
confidence: 99%